(untitled) (Medical Forum Monthly, 2024)
Background: Today diabetes is a global problem. Insulin play an inportant role in the lipid and lipoprotein metabolism. Glycemic control improves and may even normalize triglyceride and HDL cholesterol level in diabetic petients, therefore one could speculate the improvement of glycemic control beneficidly influence LDL phenolype. The degree of hyperglycemia was assesed by means of measmement of fasting blood glucose and glycosylated heamoglobin (Haemoglobin A1c). Objective: To compare the lipid profile in good glycemic controlled NIDDM type 2 with glycemic uncontrolled NIDDM type 2 and matched controls. Study Design: Comparative study Place and Duration of Study: This study was conducted at BMSI, JPMC, Karachi from June 2007 to December 2007. Materials and Methods: Total 120 subject of either sex, age were included with set criteria in study and were distributed in to three groups. GroupA controls, GroupB glycemic controlled type 2 NIDDM using oral hypoglycemic drugs regularly – GroupC glycemic uncontrolled type 2 NIDDM using oral hypoglycemic drugs regularly. Lipid, lipoprotein and fasting serum sugar and HbA1C were analyzed. Result: Highly significantly increase in total chelestrol, triglycerides and LDL cholestrol, while significantly decrease in HDL cholestrol in glycemic uncontrolled type 2 NIDDM . Conclusion: Fasting serum glucose level and HbA1c are useful diagnostic index for glycemic controlled and uncontrolled type 2 NIDDM – patient with glycemic uncontrolled type 2 NIDDM have greater disbances in lipid and lypoprotein metabolism which leads to atherosclerosis which futher results in coronary, cerebral and peripheral vascular occlusion